Review on Graphene Application: Focus on Application as Additive in Internal Combustion Engine - Sarbani, Daud; Mohd Adnin, Hamidi; R., Mamat (2021)
With new development in material sciences, many researchers have shown an increased interest in graphene. With the finding of the new production method, graphene has created breakthrough applications in composite materials, biomedical, water filtration, and energy sector. It also has been applied in many energy applications and proven to be successful. The purpose of this article is to review the application of graphene in the energy sector. The properties of graphene are then compared with other nanomaterials such as graphene oxide and carbon nanotubes. The application of the material is then examined more specifically in the internal combustion engine application. Numerous studies experimented the graphene application in diesel engines. However, there are limited experiments of graphene application in spark-ignition engines. Hence, we need to explore more the graphene applications in the energy sector for example by adding it into gasoline to improve the performance of the spark-ignition engine.